Atavisms in the avian hindlimb and early developmental polarity of the limb. Issue 9 (1st March 2021) - Bonatto Paese, Christian L.; Hawkins, Michael Brent; Brugmann, Samantha A.; Harris, Matthew P.
Abstract: Background: The naturally occurring chicken mutant talpid 2 ( ta 2 ), best known for its limb and craniofacial defects, has long served as a valuable tool for developmental biologists studying growth and patterning of craniofacial structures and the limb. The mutant provides a unique tool to examine the molecular and cellular processes regulating limb development. Results: This mutant also provides unique insights into the evolution of developmental genetic programs. Previous work defined the appearance of atavistic dentition in ta 2 embryos. Herein we describe the appearance of ancestral characters of the hindlimb in embryonic ta 2 chicken embryos. Conclusion: As the ta 2 phenotype arises as a result of mutation in C2CD3 and disrupted cilia function, this mutant provides genetic and developmental insight into the causes of asymmetry in the limb and also a model for the evolution of the avian hindlimb. Key Findings: Identification of atavistic features of the hindlimb of theropod dinosaurs in a mutant chicken, talpid The talpid2 mutation is a result of defective cilia function and provides inroads into shifts into developmental regulation leading to broad correlated changes in the limb resembling ancestral states. We provide an integrated evolutionary and developmental hypothesis of patterning of the avian hindlimb from dinosaurian ancestors though alteration of Gli3 regulation.